[LB.03.20] APPLICATIONS OF RAS-EQUILIBRIUM-ANALYSIS IN THE DIAGNOSIS OF PRIMARY ALDOSTERONISM AND BIOCHEMICAL PROFILING OF HYPERTENSION. (September 2017) - Poglitsch, M.; Ahmed, A.H.; Stoller, A.; van Oyen, D.; Schwager, C.; Aigner, C.; Domenig, O.; Haschke, M.; Stowasser, M.
Abstract : Objective: RAS-Equilibrium-Analysis is a novel mass spectrometry based approach providing a comprehensive biochemical evaluation of the circulating renin-angiotensin-system (RAS) on the basis of equilibrium angiotensin levels and circulating aldosterone. In contrast to previous technologies involving complex sampling procedures, RAS-Equilibrium-Analysis combines the robustness and accuracy of LC-MS/MS based quantification with the versatility of serum sample collection to generate a highly reproducible readout containing multiple layers of information regarding the biochemical features of the circulating RAS and its crosstalk with target tissues. Design and method: Equilibrium Angiotensin I, Angiotensin II and Aldosterone were simultaneously quantified in 500 μl of standard collected serum samples from healthy volunteers or hypertensive patients receiving different anti-hypertensive drugs. Stable-isotope labeled internal standards were used to control for analyte recovery and calibrators were prepared in the original sample matrix. Following analyte extraction, samples were subjected to UPLC-MS/MS analysis and diagnostic ratios were calculated. The reproducibility and routine compatibility of the assay was investigated in serum samples from healthy volunteers. Results: ACE inhibitor therapy resulted in a significant reduction of the ratio between equilibrium Angiotensin II and Angiotensin I, which was accompanied by an up-regulation of renin, as expected. Surprisingly, PRA highly correlated with the sum of equilibrium levels of Angiotensin I and Angiotensin II, which was independent of drug treatment. While the ARR was strongly suppressed in the presence of ACE inhibitor treatment, the Aldosterone-to-Angiotensin II-Ratio (AA2-Ratio) was not significantly affected, suggesting that ACE inhibitors would not interfere with PA screening. Conclusions: RAS-Equilibrium-Analysis is a mass spectrometry based screening assay to assess RAS activity via a highly reliable renin surrogate (Ang I + Ang II), monitor ACE activity and ACE inhibitor therapy efficacy (Ang II/Ang I-Ratio), while providing a diagnostic value for primary aldosteronism (AA2-Ratio), that reflects an advanced marker for renin mediated aldosterone secretion, which is not suppressed by ACE inhibitor therapy and might pave the way for PA screening without withdrawing anti-hypertensive drugs.